2008
DOI: 10.1557/jmr.2008.0199
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of spherical particles with mixed amorphous/crystalline nanostructured cores and insulating oxide shells

Abstract: By spark-eroding Fe75Si15B10 in water/ethanol mixtures, spherical particles with nanostructured cores consisting of mixed amorphous and crystalline phases were produced. The relative volume fractions of the amorphous and crystalline phases were dependent on the water/ethanol ratio. In the same process, continuous oxide layers were formed on the particle surfaces. The basic mechanisms responsible for the formation of the surface oxide layers and the core nanostructures were modeled. At frequencies ranging from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Further studies aimed at studying the method of electrospark erosion confirmed the possibility of obtaining nanoparticles of various conductive materials, including complex composition [8,9]. Investigations of the influence of dielectric liquid media used in the synthesis of nanoparticles [10], including cryogenic liquids [11], have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies aimed at studying the method of electrospark erosion confirmed the possibility of obtaining nanoparticles of various conductive materials, including complex composition [8,9]. Investigations of the influence of dielectric liquid media used in the synthesis of nanoparticles [10], including cryogenic liquids [11], have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…It was also substantiated that electric-spark machining can be a promising method for dispersion of the refractory, superhard and ductile metals, alloys and composites to obtain micro-and nanoparticles with unique operational properties [3,6,8]. This method allows to obtain powder micro-and nanostructured magnetic materials with shape memory [9], dispersion-strengthened refractory alloys [10,11], surface active hydroxides, oxides, carbides, and nitrides [8][9][10][11]. The possibility of processing industrial metal waste into highly dispersed powders with a highly developed active surface increased the relevance of this line of research.…”
mentioning
confidence: 99%
“…Іскро-та плазмоерозійна обробка шарів металевих гранул (ШМГ) в робочих рідинах є основою чотирьох основних груп технологічних процесів. До першої відноситься виробництво мікродисперсних порошків металів і сплавів із спеціальними властивостями: тугоплавких і жароміцних [1], з магнітною [2] і температурною [3] пам'яттю форми, з аморфною [4] та аморфно-кристалічною структурою [5], з гігантським магніторезистивним ефектом [6], магнітом'яких [7], воденьсорбуючих, надтвердих [8], корозійно стійких [9] та ін. [10][11][12].…”
unclassified